Gelling process for sodium alginate: New technical approach by using calcium rich micro-spheres. (10th December 2015) - Vicini, Silvia; Castellano, Maila; Mauri, Marco; Marsano, Enrico
Highlights: Novel method for obtaining a controlled gelling process of alginate. Electrospray system to create Ca 2+ rich micro-spheres. Rheological measurements depend on Ca 2+ /alginate ratio and micro-spheres number. Swelling properties significantly depend on the Ca 2+ /alginate ratio. Abstract: Alginate based materials have become an important class of products in many fields from the pharmaceutical industry to tissue engineering, because of their ability to create stimuli responsive hydrogels. We present a new technical approach for obtaining a controlled gelling process, based on the quantities of Ca 2+ rich alginate micro-beads added as crosslinkers. The gels have been evaluated in light of the amount of Ca 2+ added to the alginate solution, and in light of the different dimensions of the micro-beads, using rheological measurements to assess the variation in the storage modulus ( G ′), loss modulus ( G ′′) and complex viscosity ( η * ) as well as swelling and deswelling tests. The methodology was developed to obtain a material with specific characteristics for application in the field of conservation. The material had to be able to create a stable gel after being applied on the artwork surface and to confine the solvent action at the interface during cleaning operations.